Quality of nursing care: Predictors of patient satisfaction in a national sample - Fawzi Al‐Hammouri; Khaldoun M. Hamdan; Abdullah M. Haymour; Malak O. Ibrahim; Adeeb Malkawi; Sakher S. Al‐Hiary; Maha Alkaid Albqoor; Abeer M. Shaheen (Wiley, 2024)
Abstract Aim To assess patients' satisfaction with the quality of nursing care and the relationship between patients' characteristics and their level of satisfaction. Design A descriptive correlational cross‐sectional design was used in this study. Methods Convenient sampling was utilized to include 1014 inpatients from six hospitals in Jordan: three private hospitals; two governmental hospitals; and one university‐affiliated hospital. The data collection process occurred from September 2022 to January 2023. The data were collected using the Arabic version of the Patients' Satisfaction with Nursing Care Quality Questionnaire. The data were analysed using Pearson correlation, t‐test, one‐way ANOVA and multiple hierarchal regression. Results The study included 1014 patients with an average age of 51.3 (SD = 18.6), and 59.9% were females. More than two thirds of the sample reported having health insurance, and 62.7% were unemployed. The mean total score of patients' satisfaction with nursing care quality (NCQ) was 68.2 (SD = 12.9), indicating high satisfaction. Higher‐income levels (p < 0.001), higher education levels (p = 0.003), having health insurance (p < 0.001), being admitted to private hospitals (p < 0.001), being admitted to critical care units (p = 0.002), being in a single room (p = 0.001), excellent perceived health status (p < 0.001) and willingness to recommend the hospital to family and friends (p < 0.001) were significant predictors of patients' satisfaction with NCQ. Conclusions Patient and hospital environment characteristics affected patients' satisfaction with NCQ. Hospital management should consider these characteristics to improve patient satisfaction and outcomes. Implications for the Profession and/or Patient Care Policymakers and hospital management should consider improving the physical environment of their facilities to improve patients' satisfaction. Continuous professional development should emphasize nurses' communication skills to enhance their abilities to deliver information to their patients. Impact This study examined levels and predictors of patients' satisfaction with the quality of nursing care. The results indicated that improving patients' satisfaction can be achieved by focusing on areas of nurses' communication skills and explaining information to patients. Reporting Method The study adhered to STORBE guidelines for reporting observational studies. Patient or Public Contribution Hospitalized patients contributed to the data of this study. Hospital administrators facilitated its implementation.